Delfim Maya: Processos de recuperação e divulgação de um património artístico esquecido - Loureiro, Leonor da Costa Pereira (2019)
Delfim Maria de Sousa Maya (1886- 1978) was an autodidact Portuguese artist, that began his artistic work through drawing and painting but developed his originality through metal foil sculpture. His work reveals a connection and interest to Ribatejo region and the tauromachic livelihood. The sculptures reveal an eximious three-dimensional work throughout a vigorous anatomical and movement component. His work has been poorly studied and released due to different historical circumstances. This article gives a global window of the work so far produced by the Project Delfim Maya within three fields: the research for conservation and restoration of paper objects, the disclosure mechanisms, and the educational level. This Project was born by the hand of Maria José Maya, and her wish to preserve her grandfather’s collection to future generations, a singular one within the National context.